2002
DOI: 10.1080/09687590220139883
|View full text |Cite
|
Sign up to set email alerts
|

Disability Discourses for Online Identities

Abstract: Bene cial effects of the online medium have been reported for disabled people in terms of providing a 'levelling ground' where they can be treated on their merits as a person, rather than as a disabled person. If this occurs because impairment is invisible online, how then are disabled people managing disability disclosure within this social context? This paper addresses this issue discursively. Participants were recruited from various disability organisations in New Zealand and were invited to take part in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 23 publications
(18 reference statements)
3
67
0
2
Order By: Relevance
“…Identity issues on Facebook were investigated by Zhao et al [93] who suggested their participants enjoyed putting things they were proud of on Facebook and the promotion of an ideal self-image had concrete consequences within the offline world. One of the online benefits for people with disabilities was argued by Bowker and Tuffin [94] to be enhanced choice over self-representation, which was also supported by Clarke et al [95] who found AAC technology supported participant perceptions of being able to say what they liked and tell jokes. One of the challenges faced by young adolescents who use AAC was identified by Tavares and Peixoto [96] shown reduced social participation opportunities for people with cerebral palsy [41][42][43][44][45][46].…”
Section: Consequencessupporting
confidence: 53%
“…Identity issues on Facebook were investigated by Zhao et al [93] who suggested their participants enjoyed putting things they were proud of on Facebook and the promotion of an ideal self-image had concrete consequences within the offline world. One of the online benefits for people with disabilities was argued by Bowker and Tuffin [94] to be enhanced choice over self-representation, which was also supported by Clarke et al [95] who found AAC technology supported participant perceptions of being able to say what they liked and tell jokes. One of the challenges faced by young adolescents who use AAC was identified by Tavares and Peixoto [96] shown reduced social participation opportunities for people with cerebral palsy [41][42][43][44][45][46].…”
Section: Consequencessupporting
confidence: 53%
“…Access and use of ICT provide an opportunity for people with disability to communicate and interact with others and gain a sense of equality and inclusion. Bowker and Tuffin (2002) interviewed people with disability from New Zealand to explore the meaning of "choice to disclose" in online media. They found the flexibility of online media provided control over people with disability's disclosure of impairment, an opportunity not typically available in real world social interactions.…”
Section: Theme 2: Inclusion Exclusion and Empowermentmentioning
confidence: 99%
“…In Bowker and Tuffin's (2002) study, participants also mentioned that when they disclose their disability, this disclosure has much less effect on the communication compared to conversations in offline settings. Even if the communicators are informed about the disability, they are not permanently confronted with it because it is not visible in the exchanged texts.…”
Section: The Role Of Anonymity and Identitymentioning
confidence: 99%
“…Not only for other people, but also for people with disabilities themselves, social interaction in online communities offers a "mental break" from their condition. Having the control over the degree, time and pace in which they choose to inform other members of the online community about their disability offers a choice to people with disabilities that they often do not have in offline settings (Bowker and Tuffin 2002). The equalizing character of online communications and the opportunity to alter the characteristics of one's online identity (e.g., Turkle 1995) seem to be of special value for people with disabilities.…”
Section: The Role Of Anonymity and Identitymentioning
confidence: 99%
See 1 more Smart Citation